Application of Flower-Like ZnO Nanorods Gas Sensor Detecting SF6 Decomposition Products. (31st January 2013) - Peng, Shudi; Wu, Gaolin; Song, Wei; Wang, Qian
Abstract : Gas insulated switchgear (GIS) is an important electric power equipment in a substation, and its running state has a significant relationship with stability, security, and reliability of the whole electric power system. Detecting and analyzing the decomposition byproducts of sulfur hexafluoride gas (SF6 ) is an effective method for GIS state assessment and fault diagnosis. This paper proposes a novel gas sensor based on flower-like ZnO nanorods to detect typical SF6 decompositions. Flower-like ZnO nanoparticles were synthesized via a simple hydrothermal method and characterized by X-ray powder diffraction and field-emission scanning electron microscopy, respectively. The gas sensor was fabricated with a planar-type structure and applied to detect SF6 decomposition products. It shows excellent sensing properties to SO2, SOF2, and SO2 F2 with rapid response and recovery time and long-term stability and repeatability. Moreover, the sensor shows a remarkable discrimination among SO2, SOF2, and SO2 F2 with high linearity, which makes the prepared sensor a good candidate and a wide application prospect detecting SF6 decomposition products in the future.